Promoting children development through community involvement in toy library - Badzis, Mastura; Nordin, Abu Bakar; Mustafa, Sali Zaliha (Fakulti Pendidikan Universiti Malaya, 2012)
As toys have great potential to mould the character and temperament of young children, to stir imagination and to stimulate creativity and to improve the power of observation and concentration, investment in toy libraries is of great value. At present it is estimated there are more than 4,500 toy libraries in 31 countries on all continents. In Malaysia, prior to 2006, toy libraries numbered about 10-15. In 2006, the i-play Community Toy Libraries was conceptualized and set up primarily as an integrated community service center offering opportunities for families to engage fun with their children in an interactive play environment. Since the establishment of this pilot project questions were raised as to what extent the objectives in setting up these libraries were achieved. Employing the Stufflebeam (2006) Context, Input, Process, Product evaluative model this study attempted to assess the intervention process in the forms of the availability of the inputs, the efficiency of the process, and the effectiveness of the products. The findings show that toy libraries are believed to be the centers that can play important roles in strengthening relationship among individuals in the community particularly with regard to children’s well-being. Children’s participation in the planned and free activities had very good impacts on their cognitive, physical, and social development while the involvement of the parents and the community was found to be very encouraging. Recommendations were made to explore and liberalize the definition used for toy libraries and set up more toy libraries in marginalized areas.